2009
DOI: 10.1029/2008ja013624
|View full text |Cite
|
Sign up to set email alerts
|

HF radar polar patch and its relation with the cusp during BY‐dominated IMF: Simultaneous observations at two altitudes

Abstract: Recent studies have shown that the motion of the cusp can be deduced from the energetic neutral atom signals detected in the magnetosphere by the Low Energy Neutral Atom (LENA) imager on the IMAGE spacecraft. We use this approach to understand the characteristics of the formation of a polar patch seen in the dayside ionosphere. During a period of the 28 March 2001 LENA cusp signal event, the SuperDARN radars at Syowa East, Syowa South, and Kerguelen Island identified large‐scale features of a polar patch. A re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…Polar cap patches are large regions of enhanced F region plasma density with scale sizes on the order of 100-1000 km and plasma densities ranging from about 2 to 10 times the background density [e.g., Pedersen et al, 1998]. The patches can be observed through a variety of techniques including ionosondes [e.g., Sato and Rourke, 1964;Dandekar and Bullett, 1999], optical equipments [e.g., Moen et al, 2007;Hosokawa et al, 2010], coherent radar [e.g., Taguchi et al, 2009;Thomas et al, 2013], satellite, and incoherent scatter radar [e.g., Moen et al, 2006;Zhang et al, 2013aZhang et al, , 2015. Numerous processes have been proposed to explain the detachment of daytime dense plasma from a continuous TOI as discrete patches, such as the IMF-controlled reorientation of a cusp inflow region [Milan et al, 2002], convection jets [Rodger et al, 1994], in situ plasma depletion under an intense electric field [Valladares et al, 1994], polar cap expansion and contraction [Anderson et al, 1988], expansion of the polar cap convection pattern by pulsed reconnection [Lockwood and Carlson, 1992;Carlson et al, 2004Carlson et al, , 2006, reconnection pulses associated with IMF B y leading to plasma density gradients [Lockwood et al, 2005;Zhang et al, 2011Zhang et al, , 2013a, and patches being chopped on closed field lines by upward field-aligned currents .…”
Section: Introductionmentioning
confidence: 99%
“…Polar cap patches are large regions of enhanced F region plasma density with scale sizes on the order of 100-1000 km and plasma densities ranging from about 2 to 10 times the background density [e.g., Pedersen et al, 1998]. The patches can be observed through a variety of techniques including ionosondes [e.g., Sato and Rourke, 1964;Dandekar and Bullett, 1999], optical equipments [e.g., Moen et al, 2007;Hosokawa et al, 2010], coherent radar [e.g., Taguchi et al, 2009;Thomas et al, 2013], satellite, and incoherent scatter radar [e.g., Moen et al, 2006;Zhang et al, 2013aZhang et al, , 2015. Numerous processes have been proposed to explain the detachment of daytime dense plasma from a continuous TOI as discrete patches, such as the IMF-controlled reorientation of a cusp inflow region [Milan et al, 2002], convection jets [Rodger et al, 1994], in situ plasma depletion under an intense electric field [Valladares et al, 1994], polar cap expansion and contraction [Anderson et al, 1988], expansion of the polar cap convection pattern by pulsed reconnection [Lockwood and Carlson, 1992;Carlson et al, 2004Carlson et al, , 2006, reconnection pulses associated with IMF B y leading to plasma density gradients [Lockwood et al, 2005;Zhang et al, 2011Zhang et al, , 2013a, and patches being chopped on closed field lines by upward field-aligned currents .…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the right direction of the FOV relative to the cusp injection region might be a controlling factor in the ENA detection. The importance of this factor has been pointed out by Murata et al [2007] and Taguchi et al [2009a]. Taguchi et al [2009a] have shown that when pointing in the general direction of the cusp the FOV of the LENA imager can miss the cusp signal when IMF B Z becomes strongly negative.…”
Section: Importance Of Lena Imager Fov To Cusp Ion Monitoringmentioning
confidence: 99%
“…The importance of this factor has been pointed out by Murata et al [2007] and Taguchi et al [2009a]. Taguchi et al [2009a] have shown that when pointing in the general direction of the cusp the FOV of the LENA imager can miss the cusp signal when IMF B Z becomes strongly negative. A similar possibility should be considered for a positive B Z case, which is dealt with in this paper.…”
Section: Importance Of Lena Imager Fov To Cusp Ion Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…For a similar poleward‐propagating feature, Taguchi et al . [, ] suggested that it is important that the TOI is deformed by fast azimuthal flow having less dense plasma and that the interface between the deformed TOI and the fast azimuthal flow moves poleward.…”
Section: Introductionmentioning
confidence: 99%